In-situ monitoring of the transformation of ash upon heating and the prediction of ash fusion behaviour of coal/biomass blends. (15th May 2020) - Oladejo, Jumoke M.; Adegbite, Stephen; Pang, Chengheng; Liu, Hao; Lester, Edward; Wu, Tao
Abstract: In-situ monitoring of the impacts of biomass blending and temperature on the morphology of coal ash was conducted by using a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS) coupled with a heating stage and an ash fusion analyser. It is found that the interactions between ash originated from different parent fuels affected the morphology of the ash samples derived from the blends and promoted the rapid disintegration and melting of the ash particles. This helps reveal the deformation mechanism and the decrease in ash fusion temperatures of the fuel blends. Results showed that slagging propensity was mitigated as a result of blending the coal with the AAEMs-rich biomass, which is illustrated by the ash fusibility index. Subsequently, a new prediction method based on the mineral composition of the coal and biomass was formulated to elucidate the trends observed in fusion temperature of the fuel blends. This method can be used as a tool to guide the selection of biomass to adjust fusion characteristics of fuel blends. Highlights: In-situ monitoring of morphological changes of fuel blend-derived ash was conducted. Relationship between ash fusion behaviour and morphological change was revealed. A new ash fusion prediction method based on fuels' mineral composition was proposed. The dual effects of calcium as a fluxing and stabilizing element were identified. The probable melt adjustment introduced by silicon-rich biomass was considered.